Systematic literature review on early clinical evidence for immune-resolution therapies and potential benefits to patients and healthcare providers - Klekotka, Paul; Lavoie, Louis; Mitchell, Beth; Iheanacho, Ike; Burge, Russel; Cohee, Andrea; Puckett, Joanne; Nirula, Ajay (Frontiers in Immunology, 2024)
Introduction: Several current therapies for autoimmune diseases do not provide sustained remission. Therapies that focus on the restoration of homeostasis within the immune system (i.e., immune resolution) could overcome the limitations of current therapies and provide more durable remission. However, there is no established consensus on appropriate clinical trial designs and endpoints to evaluate such therapies. Therefore, we conducted a SLR focusing on five index diseases (asthma, atopic dermatitis [AD], rheumatoid arthritis [RA], systemic lupus erythematosus [SLE], and ulcerative colitis [UC]) to explore published literature on 1) expert opinion on immune-resolution outcomes that should be measured in clinical trials; and 2) quantification of immune resolution in previous clinical trials. Methods: The SLR was conducted in accordance with the PRISMA guidelines. Embase and MEDLINE databases were systematically searched (2013–2023) for published English language articles. Conference proceedings (2020–2022) from AAD, ACR, DDW, EULAR, and EADV were searched to include relevant abstracts. The study protocol was registered in PROSPERO (CRD42023406489). Results: The SLR included 26 publications on 20 trials and 12 expert opinions. Expert opinions generally lacked specific recommendations on the assessment of immune resolution in clinical trials and instead suggested targets or biomarkers for future therapies. The targets included TSLP in asthma; Th2 and Th22 cells and their respective cytokines (IL-4R and IL-22) in AD; inhibitory/regulatory molecules involved in T-cell modulation, and PTPN22 in RA; low-dose IL-2 therapy in SLE; and pro-resolution mediators in UC and asthma. In the interventional studies, direct biomarker assessments of immune resolution were the number/proportion of Treg and the ratio Th17/Treg in SLE and RA; the number of Tfh, Th1, Th2, Th17, and Th22 in AD, RA, and SLE; and mucosal proinflammatory gene signatures (TNF, IL1A, REG1A, IL8, IL1B, and LILRA) in UC. Several studies reported a statistically significant relationship between clinical remission and immune-resolution biomarkers, suggesting a link between T-cell homeostasis, cytokine production, and disease activity in autoimmune diseases. Discussion: Existing literature does not offer clear guidance on the evaluation of immune resolution in interventional studies. Further research and consensus are needed to assess a treatment's ability to induce long-term remission or low disease activity.